USING ENGLISH LANGUAGE SPEECH ASSISTANT (ELSA) SPEAK APPLICATION) TO IMPROVE STUDENTS’ OF SMP KATOLIK ST. JOHANIS LAIKIT PRONUNCIATION ABILITY - Kurnia Angel Pinontoan; Noldy Pelenkahu; Meity Muntuuntu (Program Studi Pendidikan Bahasa Inggris, 2022)
This research is aimed to find out whether or not English Learning Speech Assistant ((ELSA) Speak), a smartphone application can be used as a teaching media to improve the pronunciation ability of students of SMP Katolik St. Johanis Laikit pronunciation ability. This research using quantitative approach through the experimental method by used Pretest-Posttest Design. The sample taken from the students of 8th grade at SMP Katolik St. Johanis Laikit that consist of 20 students. The instrument tests that used in this research to collect the data are oral tests by giving 20 questions to the students on the pre-test and the 15 same questions that are valid on the post-test. Based on the result, in the pre-test one student got the highest score that is 8 and three students got the lowest score that is 2, in the post-test five students got the highest score that is 10 and one students got the lowest score that is 5. The mean score on the pre-test is 4.6 and the mean score on the post-test is 7.9. From all the results the researcher concluded that the use of appropriate teaching media can affect students’ learning outcomes that is alsocan be concluded that students’ pronunciation ability has significantly improved after using the teaching media.